(untitled) (KULT_online, 2014)
This volume presents insights into new findings on moral overridingness, a debate (re)introduced to meta-ethics in the early 1980s. Even though it gathers only seven contributions, they offer a wide range of positions on and approaches to the question of whether the demands of morality can be considered categorical. For that matter the different authors – all distinguished philosophers – not only disagree about the answer to that question, but also about its very content and significance.